Inhibitor-induced dimerization of an essential oxidoreductase from african trypanosomes - Wagner, Annika; Dirdjaja, Natalie; Krauth-Siegel, Renate (Angewandte Chemie. International edition, 2019)
Trypanosomal and leishmanial infections claim tens of thousands of lives each year. The metabolism of these unicellular eukaryotic parasites differs from the human host and their enzymes thus constitute promising drug targets. Tryparedoxin (Tpx) from Trypanosoma brucei is the essential oxidoreductase in the parasite's hydroperoxide-clearance cascade. In vitro and in vivo functional assays show that a small, selective inhibitor efficiently inhibits Tpx. With X-ray crystallography, SAXS, analytical SEC, SEC-MALS, MD simulations, ITC, and NMR spectroscopy, we show how covalent binding of this monofunctional inhibitor leads to Tpx dimerization. Intra- and intermolecular inhibitor-inhibitor, protein-protein, and inhibitor-protein interactions stabilize the dimer. The behavior of this efficient antitrypanosomal molecule thus constitutes an exquisite example of chemically induced dimerization with a small, monovalent ligand that can be exploited for future drug design.
Gesehen am 27.05.2019